Study on Pyroelectric Harvesters Integrating Solar Radiation with Wind Power - Chun-Ching Hsiao; Jia-Wai Jhang; An-Shen Siao (Energies, 2015)
Pyroelectric harvesters use temperature fluctuations to generate electrical outputs. Solar radiation and waste heat are rich energy sources that can be harvested. Pyroelectric energy converters offer a novel and direct energy-conversion technology by transforming time-dependent temperatures directly into electricity. Moreover, the great challenge for pyroelectric energy harvesting lies in finding promising temperature variations or an alternating thermal loading in real situations. Hence, in this article, a novel pyroelectric harvester integrating solar radiation with wind power by the pyroelectric effect is proposed. Solar radiation is a thermal source, and wind is a dynamic potential. A disk generator is used for harvesting wind power. A mechanism is considered to convert the rotary energy of the disk generator to drive a shutter for generating temperature variations in pyroelectric cells using a planetary gear system. The optimal period of the pyroelectric cells is 35 s to harvest the stored energy, about 70 μJ, while the rotary velocity of the disk generator is about 31 RPM and the wind speed is about 1 m/s. In this state, the stored energy acquired from the pyroelectric harvester is about 75% more than that from the disk generator. Although the generated energy of the proposed pyroelectric harvester is less than that of the disk generator, the pyroelectric harvester plays a complementary role when the disk generator is inactive in situations of low wind speed.